Symbolic Analytical Expressions for the Solution of Hyperbolic form of Keplers Equation - Fadaaq, Mervat Abdulgader (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, symbolic analytical expressions for the solution of hyperbolic form of Keplers equation will be established .Mathematical procedure for the expressions is also established to together with some of its output.